Science et démocratie dans la gestion de la nature : des ethno-sociologues pris dans la modélisation d'accompagnement - Marie Charles; Frédérique Chlous-Ducharme; Elsa Faugère; Maurice Wintz (VertigO)
This paper presents a cross analysis of the experiences of four social scientists involved in a companion modelling approach. As part of a research project of the Institut Français de la Biodiversité, four multi-agent systems and two role-playing games were developed on Biosphere Reserves. The purpose of the project was to explore the effects of natural land cover change from previously open to closed ecosystem structures and in turn, how changes in local landscapes stimulate the emergence of new social expectations and environmental values. This contribution follows earlier work on the study of complex systems, which recognizes the inherent complexity and uncertainty of natural resource management and thus the need to overcome the unproductive cleavage between the social and natural sciences. This paper aims to provide a framework for participatory and policy relevant research. .The reflection centers first on the place of social siences in the approach, the roles played by the researchers in the different contexts and the difficulties encountered, and continues on the relationship between society and nature.